Sustainability of smallholder quinoa production in the Peruvian Andes (2020)
Since 2010, as a result of the increased attention to quinoa as a highly nutritious crop and increased international demand, the acreage and production of quinoa expanded rapidly in the Andes region. Global demand and price increases create opportunities for smallholder Andean farmers but also concerns on the environmental impacts of quinoa acreage expansion and the changing quinoa production practices of smallholder farmers. In this paper, we assess the sustainability performance of smallholder quinoa production in the Junín region in the central highlands of Peru. We use primary data from a two-round survey among 367 smallholder farmers in the Junín region and secondary data from Ecoinvent and LCFoods databases. We use a combination of a life cycle assessment to assess the various environmental impacts of quinoa production; a data envelopment analysis to link the environmental performance of quinoa production with the economic performance, and quantify the eco-efficiency of individual farms; and a fractional regression model to examine the heterogeneity in eco-efficiency across farms. We find that conventional quinoa production creates a global warming potential of 7.82 kg CO2-equivalent per kg of protein, which is comparable to the environmental impact of organic quinoa production and production of other grain crops but much below the impact of production of rice and food from animal origin. Also, the eco-efficiency among smallholder quinoa producers is low, on average 18.2%, and that excessive use of mineral fertilizers and a switch to mechanical threshing explains this low eco-efficiency. We conclude that quinoa, with its specific nutritional characteristics, can make a contribution to a more sustainable global food production but that attention is needed to the soil fertility management practices of smallholder Andean farmers in order to reduce the environmental impact and increase the efficiency of smallholder quinoa production.